Analysis of the Effectiveness of 2D Animation as a Medium to Increase Awareness of Bullying among Generation Alpha in Indonesia - Jimmy Pratama; Louis Zeng; Deli Deli (IJOEM: Indonesian Journal of E-learning and Multimedia, 2026)
Background: Bullying among elementary school children in Indonesia has become a serious issue that affects the emotional and mental development. Traditional methods such as lectures are often ineffective in capturing children’s attention, especially for Generation Alpha, who are more familiar with visual and digital learning styles.Aims: This study aims to analyze the effectiveness of 2D animation as an educational medium to increase awareness of bullying among Generation Alpha in Indonesia.Methods: The research employed a Research and Development (R&D) approach using the Multimedia Development Life Cycle (MDLC) model, consisting of six stages: concept, design, material collection, assembly, testing, and distribution. The effectiveness of the animation was evaluated using the EPIC Model (Empathy, Persuasion, Impact, and Communication) with a quantitative descriptive analysis involving 400 respondents.Results: The findings indicate that all EPIC model dimensions achieved high effectiveness levels, with an average score of 4.94 (on a 5-point scale), showing that 2D animation successfully conveyed anti-bullying messages. The media demonstrated high perceived effectiveness in stimulating empathy, increasing understanding, and improving communication regarding bullying prevention.Conclusion: 2D animation is an effective educational tool for promoting empathy and awareness about bullying among Generation Alpha in Indonesia. The study supports integrating animation into character education programs to foster social and moral awareness at an early stage.